When shared pain is not half the pain: enhanced central nervous system processing and verbal reports of pain in the presence of a solicitous spouse: research paper - Nees, Frauke; Ditzen, Beate; Flor, Herta (Pain, 2022)
The experience of pain and pain behaviors is not only determined by physiological but also psychosocial factors. In this context, the learning history of the individual and specifically operant reinforcement related to spouse responses might play an important role. We investigated the effect of a solicitous and habitually pain-reinforcing spouse for the processing of pain in patients with chronic pain. Using multichannel electroencephalography, pain behaviors, and self-reports of pain, we examined 20 patients with chronic back pain (10 with solicitous and 10 with nonsolicitous spouses) and 10 matched healthy controls. The participants received a series of painful and nonpainful electrical stimuli applied to the site of pain (back) and a control area (finger) in the presence vs absence of the spouse. The global field power of the electroencephalogram with a focus in the frontal region was enhanced in patients with chronic back pain who had a solicitous spouse compared to those with a nonsolicitous spouse and the healthy controls. This was specific for the painful stimulation at the back and occurred only in the presence but not the absence of the spouse. Pain ratings of intensity and unpleasantness were also higher in the patients with solicitous spouses when the spouse was present during painful stimulation. These data suggest that significant other responses indicative of operant reinforcement may have a direct effect on the cerebral processing of pain and related pain perception.